2016
DOI: 10.2507/ijsimm15(2)co9
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Inventory Strategy in a Dual-Channel Supply Chain with Transshipment Consideration

Abstract: Aimed at the possibility of stock-out of the traditional retail channel under stochastic demand in a dual-channel supply chain, we propose a cooperative inventory strategy, in which the excess demand of the traditional retail channel is complemented by the excess inventory of the manufacturer's direct channel through transshipment. We establish a newsboy model to analyse each supply chain member's order quantity decision making process, and prove the unique existence of pure-strategy Nash equilibrium under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 23 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Morris and Shin [ 9 – 11 ] have used this method to make a series of studies on the self-realization mechanism of the financial crisis and put forward policy suggestions according to the equilibrium results. Brown et al [ 12 ], Hakenes and Schliephake [ 13 ], He and Manela [ 14 ], Schilling [ 15 ], and Yang et al [ 4 ] all used game analysis methods to study the liquidity and system stability in the financial field. Some studies have also used game theory to study the interaction between suppliers and sellers in the supply chain [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Morris and Shin [ 9 – 11 ] have used this method to make a series of studies on the self-realization mechanism of the financial crisis and put forward policy suggestions according to the equilibrium results. Brown et al [ 12 ], Hakenes and Schliephake [ 13 ], He and Manela [ 14 ], Schilling [ 15 ], and Yang et al [ 4 ] all used game analysis methods to study the liquidity and system stability in the financial field. Some studies have also used game theory to study the interaction between suppliers and sellers in the supply chain [ 16 , 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…Although studies have shown that information sharing between supply chains can significantly improve product quality and business performance [ 1 ], and producers can contract design and revenue distribution mechanisms to avoid immoral behavior of suppliers [ 2 ]; there is still a gap in the research on the authenticity guarantee of credit and commodity quality at the technical level. Some studies have pointed out that blockchain is a new and revolutionary technology that significantly affects the supply chain network and discussed the significance of blockchain technology in supply chain management [ 3 , 4 ]. Therefore, nowadays, with the innovation and development of distributed ledger technology and its application in Central Bank Digital Currency (CBDC) research and development, using CBDC to support information sharing activity and solving credit and commodity quality management problems in the supply chain scenario has gradually become possible.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this, Silbermayr [31] developed a framework of multiple retailers. Different from these, Yang et al [32] proposed cooperative and uncooperative inventory strategies in a dual-channel system with customer switching. ey proved the existence and uniqueness of a Nash equilibrium under both strategies, and they also investigated the effects of the transshipment cost and the channel substitution rate on the optimal order quantities under each inventory strategies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies on channel synergy mainly focused on this field. Scholars propose many channel synergy strategies, such as cooperative advertising strategy [17,18], lateral transshipment strategy [19][20][21], and information sharing strategy [22][23][24]. They all found that in some cases, these channel synergy strategies can improve the performance of manufacturer and retailer simultaneously.…”
Section: Literature Reviewmentioning
confidence: 99%